Closed vs Open‐Shell CTV Based Host Compounds: A Direct Comparison. Issue 19 (29th November 2016) - Lefevre, Sara; Simonet, Raphaël; Pitrat, Delphine; Mulatier, Jean‐Christophe; Vanthuyne, Nicolas; Jean, Marion; Dutasta, Jean‐Pierre; Guy, Laure; Martinez, Alexandre
Abstract: New hemicryptophane compounds combining a cyclotriveratrylene (CTV) unit, three binaphthol moieties in the linkers and closed by a simple benzene unit have been synthesized enantiomerically and diastereomerically pure. Assignment of their absolute configuration was achieved by chemical correlation. These closed shell host compounds were then tested in the recognition of carbohydrates and compared with their open‐shell counterparts. Closing the molecular cage induces a slight drop in affinity, associated with an improvement in the stereoselectivity of the recognition process, probably related to the higher preorganization of the cage compounds. Abstract : Advantages and drawbacks of both open and closed host compounds including a CTV unit are here discussed: when used ad receptor for carbohydrates, closing the molecular cage induces a slight drop in affinity, associated with an improvement in the stereoselectivity.